Evidence-based Medical Monitoring: From Principles to Practice - Glasziou, P; Irwig, L; Aronson, J (Blackwell Publishing Ltd., 2008)
Monitoring is a major component of management of chronic diseases such as diabetes, cardiovascular disease, arthritis and depression. Yet poor monitoring means healthcare costs are rising. This book discusses how monitoring principles adopted in other spheres such as clinical pharmacology and evidence-based medicine can be applied to chronic disease in the global setting. With contributions from leading experts in evidence-based medicine, it is a ground-breaking text for all involved in delivery of better and more effective management of chronic illnesses. © 2008 Blackwell Publishing.